BETTER TEACHING AND LEARNING (BTL) UNTUK MENINGKATKAN PENGAJARAN PROFESIONAL DAN PEMBELAJARAN BERMAKNA MAHASISWA - Rahayu Pristiwati (Universitas Negeri Semarang, 2013)
This study is conducted to describe the quality of improvement process in course designed by Better Teaching and Learning (BTL) in the course of learning process to speak on student’s university participants in Learning Speaking, decrypt improving the quality of student’s learning outcomes after learning speak courses to Better Teaching and Learning (BTL), and express the student’s respone as feedback of learning outcomes assessment that designed to reveal the performance of the Better Teaching and learning (BTL) which can provide significant feedback to positive student’s response. The subjects of this study are the students of Indonesian Language and Literature Education. Learning is implemented using Better Teaching and Learning (BTL). Method of collecting the data is by using observation, assessment rubrics, interviews, journals, and photos. The process and the students’ learning outcomes were analyzed with qualitative and quantitative techniques. The results show that the process, learning outcomes, and student’s responses can be enhanced through implementation of Better Teaching and Learning (BTL) which are arranged in fourteen steps.